Uncommon Surgical Emergencies in the Adult Gynecologic Patient: Two Cases of Missed Diagnosis of Outflow Tract Obstruction from Congenital Uterine Anomalies - Bailey McGuinness; Natalia Llarena; Tommaso Falcone; Elliott G. Richards (Case Reports in Obstetrics and Gynecology)
Gynecologic emergencies may result from congenital uterine anomalies (CUAs) with outflow tract obstruction. Not limited to the “classic” presentation of an adolescent amenorrheic pain patient, such anomalies should be part of the differential diagnosis for adult female patients presenting with severe pelvic pain. Obstructed rudimentary noncommunicating cavitary horns may result in severe chronic or acute pain and necessitate urgent surgical management. While two-dimensional (2D) ultrasound is often the initial diagnostic tool, three-dimensional (3D) ultrasound and MRI can accurately delineate CUAs for definitive diagnosis. When excision of a rudimentary horn is required, a laparoscopic approach is preferable. This case series focuses on two adult patients with severe pelvic pain due to unicornuate uteruses with obstructed noncommunicating cavitated rudimentary horns. Both cases involve a delayed diagnosis, the inability to make the diagnosis at standard surgical observation, and the resultant need for urgent surgical management.